2006
DOI: 10.2118/82249-pa
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Total Skin Factor in Perforated Wells

Abstract: In this study, the available methods and software to predict the well productivity and total skin factor in fully perforated vertical wells have been reviewed. The methods have been compared against the experimental data obtained on an electrolytic apparatus, and their accuracy has been investigated. It has been observed that the 3D semianalytical model, SPAN 6.0 software, and the simple hybrid model described in this paper replicate the experimental results very well. On the other hand, the results estimated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(17 citation statements)
references
References 32 publications
1
16
0
Order By: Relevance
“…They compared their solutions with the middle point, equivalent-pressure point, and pressure-averaging solutions given in the petroleum literature. In addition to the recent Biryukov and Kuchuk (2012) paper, a few other papers were also published on selectively perforated and/or completed wells, i.e., wells with multiple production slots (ring slots along the wellbore), specially Spivak and Horne (1983), Larsen (1993), Yildiz and Cinar (1998), Tang et al (2000), Yildiz (2002aYildiz ( , b, 2004Yildiz ( , 2006a. The Spivak and Horne (1983) vertically slotted-liner solution, which is obtained from the uniform-flux solution, is somewhat similar to the solutions given in this paper.…”
Section: Introductionsupporting
confidence: 67%
“…They compared their solutions with the middle point, equivalent-pressure point, and pressure-averaging solutions given in the petroleum literature. In addition to the recent Biryukov and Kuchuk (2012) paper, a few other papers were also published on selectively perforated and/or completed wells, i.e., wells with multiple production slots (ring slots along the wellbore), specially Spivak and Horne (1983), Larsen (1993), Yildiz and Cinar (1998), Tang et al (2000), Yildiz (2002aYildiz ( , b, 2004Yildiz ( , 2006a. The Spivak and Horne (1983) vertically slotted-liner solution, which is obtained from the uniform-flux solution, is somewhat similar to the solutions given in this paper.…”
Section: Introductionsupporting
confidence: 67%
“…These numerical simulations culminated in the semi-analytical productivity solution developed by Karakas and Tariq (1991). Although several notable efforts were made to improve the model with numerical and analytical solutions (Dugolu, 1998;Anseh et al 2002;Yildiz, 2006;Atkinson et al 2009;Sun et al 2011), no major issues have been identified. A few discrepancies between the model and numerical simulation results were primarily because of different, usually unrealistic, assumptions used in the numerical simulations rather than defects of the semi-analytical model.…”
Section: Introductionmentioning
confidence: 99%
“…The flow efficiency of the FPWs has been the subject of many investigations. [13][14][15][16][17][18][19][20][21][22][23][24][25] The effect of ideal perforating has been quantified in terms of perforation pseudoskin, .…”
Section: Introductionmentioning
confidence: 99%
“…24 Recently, the McLeod method, the Karakas-Tariq algorithm, Jones-Slusser method, SPAN software, and the 3D analytical solution were compared against the experimental data. 25 It has been shown that 1) the McLeod method underestimates the perforation total skin, 2) the Karakas-Tariq method for perforation pseudoskin works fine, however, the Karakas-Tariq algorithm overpredicts perforation total skin in the presence of formation damage and crushed zone, 3) the 3D analytical solution and SPAN software replicate the experimental data very well, and 4) the Jones-Slusser model, which does not consider the effect of compacted zone, agrees well with the 3D analytical solution and SPAN software when the crushed zone is also ignored in the 3D solution and SPAN.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation